Pancreatic Perivascular Epithelioid Cell Tumour Presenting with Upper Gastrointestinal Bleeding - Christos Petrides; Kyriakos Neofytou; Aamir Z. Khan (Case Reports in Oncological Medicine)
PEComa is a family of rare mesenchymal tumours which can occur in any part of the human body. Primary PEComas of the pancreas are extremely rare tumours with uncertain malignant potential. A 17-year-old female was admitted to the hospital due to melena. She required several transfusions. CT scan demonstrated a mass at the head of the pancreas measuring 4.2 cm in maximum diameter. An endoscopic ultrasound showed an ulcerating malignant looking mass infiltrating 50% of the wall of the second part of the duodenum in the region of the ampulla. Multiple biopsies taken showed extensive ulceration with granulation tissue formation and underlying large macrophages without being able to establish a definite diagnosis. We proceeded with pylorus-preserving pancreaticoduodenectomy. The postoperative course of the patient was unremarkable, and she was discharged on the 8th postoperative day. Histology examination of the specimen showed a PEComa of pancreas. Eighteen months after resection the patient is disease free. To the best of our knowledge this is the first time we describe a case of a pancreatic PEComa presenting with massive gastrointestinal bleeding.